Rapidly progressive dyspnea in an elderly diabetic - Nithish M Bhandary; Vishnu Sharma; S N Megha (Journal of Advanced Lung Health, 2021)
Breathlessness is a common presenting symptom in the emergency room. Focused history, clinical examination, and proper stepwise evaluations are essential for early diagnosis and treatment. The most common presenting feature of nCovid19 pneumonia is rapidly progressive breathlessness. During this pandemic, we need to differentiate nCovid19 pneumonia from other causes for breathlessness. Here, we discuss the differential diagnosis for rapidly progressive breathlessness, how to evaluate a patient with suspected nCovid19 pneumonia and the role of chest computed tomography scan in nCovid19.